Split-gate trench metal-oxide-semiconductor field effect transistor with an inverted L-shaped source region. (December 2022) - Fang, Dong; Yang, Guang; Qiao, Ming; Xiao, Kui; Yang, Xiangyu; Bian, Zheng; Zhang, Bo
Abstract: In this work, an inverted L-shaped source region (ILS) structure is proposed and studied to improve switching performance of split-gate trench metal-oxide-semiconductor field effect transistor (SGTMOS). The ILS structure is formed by a control gate over etch step followed by a self-aligned implantation afterwards. The ILS structure eliminates the coupled area between the control gate electrode and the highly doped n-type implanted source region. As a result, the gate to source capacitance (Cgs ) is significantly reduced and a relatively low gate charge (Qg ) can be achieved. At the meantime, specific on-resistance (Ron, sp ) almost remains, resulting in a considerable figure of merit (FOM, Ron, sp  × Qg ) reduction. Simulations and experiments were made to verify the theory. The proposed SGT with the ILS structure achieves an excellent switching FOM, which is smaller than conventional SGT, but almost without impacting other fundamental parameters.